REGIONAL ARRANGE IN THE PROVINCE OF WEST JAVA: A FORMULATION POLICY - Gunawan Undang; Eny Nuryani Resmiawati; Taufiq Alamsyah; Dina Dina (Sosiohumaniora, 2022)
This study analyzes regional structuring policies with the formation of candidates for the New Autonomous Region (DOB) in West Java Province. The territorial arrangement is considered important to improve public services, increase welfare, equitable development, and bring the span of control closer. There are currently 27 district and city governments in West Java Province that are considered unequal to serve 49.94 million inhabitants (2020). Several problems and the imbalance between the number of regions and the population (1: 1.85 million) require policy formulation. The method used in this study is the tailor-made method. Collecting data using participatory observation techniques, in-depth interviews, and documentation. Although the conclusions of this study are still preliminary findings (new paradigm), based on the tailor-made method that we use (Lee, 2006; Milotay, 2016; Pawson & Wong, 2013; Rohmadin et al., 2017) it is hoped that it can be a major consideration in the formulation of regional structuring policies in West Java. The implication of this research is that the interests (aspirations) of the community are channel (bottom-up) and the executive and legislature in West Java Province, and the center (top-down are also actively involved so that regional planning is beneficial for improving the quality of public services and sustainable regional development. The results showed that the formulation of regional structuring policies to realize increased public services, welfare, equitable development, and control and consideration of rapid population growth is urgently needed by the West Java Provincial Government. Considering the population growth rate of 1.39% per year, the policy formulation that we recommend is to organize 27 existing regions and form 26 new autonomous regions. Until 2030, West Java Province has at least 53 regencies/cities, while in 2045 at least 65 regencies/cities.